Principal Supervisory Management in Improving the Quality of Learning at SMP - Ahmadi Sapto Nugroho; Saryanto Saryanto; Jumintono Jumintono (Journal of Creative Power and Ambition (JCPA), 2026)
This study examines principal supervisory management in improving the quality of learning at SMP Negeri 5 Satu Atap Sapuran in 2026. The research aims to analyze the processes of planning, implementation, and evaluation of supervisory management, as well as to identify the supporting factors, challenges, and follow-up actions associated with supervision practices. A qualitative descriptive approach was employed, with data collected through interviews, observations, and document analysis involving the principal, teachers, and relevant school stakeholders. The findings indicate that effective supervisory management is implemented through systematic planning, classroom observation, constructive feedback, performance evaluation, and continuous follow-up activities. These supervisory practices contribute to enhancing teacher professionalism, instructional effectiveness, and student engagement in the learning process. The study also reveals that leadership commitment, teacher motivation, resource availability, and a collaborative school culture serve as key supporting factors for successful supervision. However, challenges such as limited time, varying teacher competencies, resistance to supervision, and educational changes may hinder the effectiveness of supervisory activities. To address these challenges, the principal implements professional development programs, coaching, mentoring, collaborative learning activities, and continuous monitoring. The analysis, grounded in Instructional Leadership Theory, Clinical Supervision Theory, Transformational Leadership Theory, Organizational Change Theory, and Continuous Improvement Theory, demonstrates that supervisory management is a strategic leadership practice that promotes sustainable improvement in learning quality. Therefore, effective principal supervision plays a vital role in strengthening teacher performance, improving educational outcomes, and supporting overall school effectiveness.